Destination Buzzers: Netnographying Digital Nomads - Ioulia Poulaki; Eirini Vlassi; Eleni Mavragani; Eleftheria Chatzimichali; Andreas Papatheodorou (Tourism and Hospitality)
A new way of life and work—digital nomadism—is increasingly appealing to a growing global workforce, while many destinations are beginning to view this form of tourism not only as an economic opportunity but also as a strategic tool for mitigating seasonality and promoting sustainable destination development. This paper aims to identify the key criteria that digital nomads consider when selecting a temporary residence base, contributing to the growing body of research on digital nomadism by analysing the relative impact of various factors influencing destination choice. The originality of this study lies in its mixed-method approach, which combines secondary and primary data through a netnographic analysis of online communities and semi-structured interviews with digital nomads. Findings from the secondary data highlight the cost of living, internet quality, and lifestyle offerings of a destination as the most influential factors in nomadic decision-making. Additionally, primary data further illustrate the hierarchy of digital nomads’ needs and preferences, which are classified and prioritised based on Maslow’s hierarchy of needs. These insights carry significant implications for destination managers and tourism stakeholders. Understanding and responding to the evolving expectations of digital nomads can help destinations not only attract this emerging market segment but also design policies and infrastructure that align with principles of sustainable tourism.